Clinical profile of patients of poisoning admitted in emergency department in a teaching hospital, MAMC, Agroha, Haryana, India - Shah, Mohd Y.; Naqash, Mohd M.; Shah, Faisal Y.; Shah, Faizan Y. (International Journal of Research in Medical Sciences, 2017)
3 Million Serious poisoning (1 million accidentals and 2 million suicide attempts) occur each year worldwide. India ranks second in Asia in annual pesticide consumption. A study was conducted (1 year) wherein patients with history of poisoning were admitted from different catchment areas of hospital (30 Km radius). The total number of patients admitted during study period was 61. Patients had consumed these agents to attempt suicide. Out of 61 patients 26 were male and rest 37 were females. 18 patients died and rest survived. The precipitating factors in the suicide attempts were stranded relations with husband/wife, failure in examination and confrontation with parents. The availability of these poisonous substances in the household make people to consume these agents on slight provocation.All our patients, though majority were literate, were from families who had agricultural land and majority of their family members were farmers.